Patient health care intensive care system using wearable band sensor network. (2021) - Ramkumar, S.; Rajeev Kumar, M.; Rajalakshmi, S.; Rathi, M.
Abstract: Expanding the definition of Internet and making it more pervasive, IoT (Internet of Things) has now become the utmost active communication standard of the 21st century, allowing smooth connectivity between various types of devices. IoT has now become productive in many ways, such as banking, health care system and lot more, for this particular reason. This method helps the ambulance to be monitored by GPS. The GSM technology is used to send an SMS alert showing the patient's suspicious circumstance along with a URL to the ambulance's current location. Using sensors that can be displayed in the app, the patient's vital parameters are calculated. These parameters are body temperature, heart rate, and blood pressure, which are modified through internet access to the cloud server. In this app, the location obtained by controlling the ambulance can also be viewed. By using this approach, an acknowledgment of the patient's position and body state may be understood.